On the mechanism of recombination at oxide precipitates in silicon - Murphy, J; Bothe, K; Voronkov, V; Falster, R (2013)
Oxide precipitates are well known to degrade minority carrier lifetime in silicon, but the mechanism by which they act as recombination centres is not fully understood. We report minority carrier lifetime measurements on oxide precipitate-containing silicon which has been intentionally contaminated with iron. Analysis of the injection-dependence of lifetime demonstrates the same recombination centres exist in iron-contaminated and not intentionally contaminated samples, with the state density scaling with iron loss from the bulk. This shows that recombination activity arises from impurity atoms segregated to oxide precipitates and/or surrounding crystallographic defects. © 2013 American Institute of Physics.